2017
DOI: 10.1055/s-0037-1599195
|View full text |Cite
|
Sign up to set email alerts
|

Unusual de novo Partial Trisomy 17p12p11.2 due to Unbalanced Insertion into 5p13.1 in a Severely Affected Boy

Abstract: Gain of copy numbers can be due to different chromosomal rearrangements such as direct or indirect duplications, translocations, small supernumerary marker chromosomes, or insertions. In a 3-year-old boy with dysmorphic features and developmental delay, chromosome analyses revealed a derivative chromosome 5. Microdissection and reverse fluorescence in situ hybridization identified the in 5p13.1 inserted part as 17p12-p11.2 material. Thus the patient suffered from a rare combination of genomic disorder, that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Facial anomalies were identified in five patients, and included down-slanting palpebral fissures (2/5) with or without hypertelorism (3/5). Additionally, Mendez-Rosado et al [15] reported a patient sharing this duplication due to an unbalanced insertion in 5p13.1 (Table 1). Our patient shares some clinical characteristics with the above-described patients, including global developmental delay, short stature, hypotonia and some facial features (i.e., down-slanting palpebral fissures); however, he does not present congenital heart disease, renal abnormality or autistic features (he has no clinical difficulty with behavior, social interaction and communication) that have been characteristically reported in 70–100% of patients with PTLS [16].…”
Section: Discussionmentioning
confidence: 99%
“…Facial anomalies were identified in five patients, and included down-slanting palpebral fissures (2/5) with or without hypertelorism (3/5). Additionally, Mendez-Rosado et al [15] reported a patient sharing this duplication due to an unbalanced insertion in 5p13.1 (Table 1). Our patient shares some clinical characteristics with the above-described patients, including global developmental delay, short stature, hypotonia and some facial features (i.e., down-slanting palpebral fissures); however, he does not present congenital heart disease, renal abnormality or autistic features (he has no clinical difficulty with behavior, social interaction and communication) that have been characteristically reported in 70–100% of patients with PTLS [16].…”
Section: Discussionmentioning
confidence: 99%
“…En un caso adicional, se realizó un estudio FISH más complejo para caracterizar un cromosoma 5 derivativo. 7…”
Section: Citogenética Molecularunclassified